1999
DOI: 10.1073/pnas.96.11.6428
|View full text |Cite
|
Sign up to set email alerts
|

MSF (MLL septin-like fusion), a fusion partner gene of MLL, in a therapy-related acute myeloid leukemia with a t(11;17)(q23;q25)

Abstract: MLL (ALL1, Htrx, HRX), which is located on chromosome band 11q23, frequently is rearranged in patients with therapy-related acute myeloid leukemia who previously were treated with DNA topoisomerase II inhibitors. In this study, we have identified a fusion partner of MLL in a 10-year-old female who developed therapy-related acute myeloid leukemia 17 months after treatment for Hodgkin's disease. Leukemia cells of this patient had a t(11;17)(q23;q25), which involved MLL as demonstrated by Southern blot analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
2
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 56 publications
5
150
2
3
Order By: Relevance
“…The first clues to the role of septins in neoplasia came from the observation that balanced translocations involving septin loci and the MLL locus on chromosome 11 were seen in leukaemia giving rise to chimeric fusion proteins where the N terminus of MLL was fused, in frame, to almost the entire open reading frame of SEPT9 (Osaka et al, 1999). Subsequently, it has been found that three other septins (SEPT5, SEPT6 and SEPT11) can form very similar fusion proteins with MLL again with the N-terminal moiety of MLL fused to almost the entire open reading frame of the partner septin (Taki et al, 1999;Ono et al, 2002;Kojima et al, 2004).…”
Section: Septins and Cancer Septins: The Mll Connectionmentioning
confidence: 99%
“…The first clues to the role of septins in neoplasia came from the observation that balanced translocations involving septin loci and the MLL locus on chromosome 11 were seen in leukaemia giving rise to chimeric fusion proteins where the N terminus of MLL was fused, in frame, to almost the entire open reading frame of SEPT9 (Osaka et al, 1999). Subsequently, it has been found that three other septins (SEPT5, SEPT6 and SEPT11) can form very similar fusion proteins with MLL again with the N-terminal moiety of MLL fused to almost the entire open reading frame of the partner septin (Taki et al, 1999;Ono et al, 2002;Kojima et al, 2004).…”
Section: Septins and Cancer Septins: The Mll Connectionmentioning
confidence: 99%
“…Rk Expression GAN Description Possible function/relation to Leukemia 4 AML > ALL U59632 Cell division control related hCDCrel-1 is a partner protein (hCDCrel-1) gene of MLL in some leukemias (Osaka, 1999). mRNA 3 AML > ALL U82759 GB DEF = Homeodomain Hoxa9 collaborates with other genes to produce protein HoxA9 mRNA highly aggressive acute leukemic disease (Thorsteinsdottir, 1999).…”
Section: C> N T62947 60s Ribosomal Protein L24mentioning
confidence: 99%
“…This translocation has been identified as fusing the MLL gene on chromosome 11q23 to either the AF17q25 gene or to MSF, both located on 17q25 and differing by a single base. [31][32][33] Since the MLL gene is known to activate several HOX genes, 34 it is tempting to speculate that the fusion protein may activate BP1 in this case.…”
Section: Figurementioning
confidence: 99%